Developing and implementing a health educational package for preemie moms in the care of their baby after hospital discharge - Roshaya Zakaria; Rosnah Sutan; Rohana Jaafar (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Educating a mother of a premature baby and providing a structured written educational information can enhance better understanding and practice. This article describes the development and implementation of a health educational package for preemie moms in the care of their premature baby after neonatal intensive care unit discharge. SUBJECTS AND METHODS: The package known as "Preemie Mom: A Guide for You" was designed based on Stufflebeam's model and has four phases: (1) content evaluation from available sources of information, (2) input evaluation based on mothers' need related to premature baby care, (3) process evaluation for package designing and content drafting, and (4) product evaluation to determine its feasibility. The contents were extracted and collated for validation by consulting various specialists in related fields. A final draft was drawn based on comments given by experts. Comments from the mothers were taken for formatting, visual appearance, and content flow for easy understanding and usage. RESULTS: All ten existing articles and eight relevant documents were gathered and critically appraised. The package was designed based on 11 main components related to the care of premature baby after discharge. The content validation was accepted at a minimum score of 0.85 for the item-level content validity index analysis. Both experts and mothers were agreed that the package is easy to use and well accepted as a guide after discharge. The agreement rate by the mothers was at 93.33% and greater for the front page, writing style, structure, presentation, and motives of the package. CONCLUSIONS: "Preemie Mom: A Guide for You" is a validated health educational package and ready to be used to meet the needs of the mother for premature baby care at home.